The Gayton Scholarship: A School Story - Hayens, Herbert, 1861-1944 (Salt Lake City, UT : Project Gutenberg, 2014)
"The Gayton Scholarship: A School Story" by Herbert Hayens is a novel written in the early 20th century. The story revolves around the lives of schoolboys in the seaside town of Beauleigh, particularly focusing on Jim Hartland and his friends as they navigate the competitive environment of their school and face personal challenges. The narrative explores themes of friendship, ambition, and the consequences of one's actions. The opening of the story introduces Jim Hartland and his best friend, Dick Boden, as they prepare for an important examination associated with a coveted scholarship. The two boys are excited but also anxious, as the scholarship offers a chance for educational advancement amidst their difficult circumstances marked by Jim's father's recent tragic loss at sea. As the boys interact with various characters, including their supportive and ill parents, the excitement of competition is palpable. Just as their focus shifts to the cricket match, underlying tensions about their personal lives begin to emerge, setting the stage for future conflicts and character development throughout the book. (This is an automatically generated summary.)
Release date is 2014-06-25
Produced by Al Haines
Keywords: Boys -- Conduct of life -- Juvenile fiction; Schools -- Juvenile fiction; Scholarships -- Juvenile fiction